A first principles study of electronic and optical properties of the polar quaternary chalcogenides β-A2Hg3Ge2S8(A=K and Rb). (June 2015) - Azam, Sikander; Khan, Saleem Ayaz
Abstract: The β-A2 Hg3 Ge2 S8 (A=K and Rb) materials have a unique structure, possessing the high infrared transmission. More studies on β-A2 Hg3 Ge2 S8 (A=K and Rb) are significant to investigate the probability of using these materials for optoelectronic devices. This work presents the results dealing with electronic and optical properties of β-A2 Hg3 Ge2 S8 (A=K and Rb) obtained from first-principles calculations. We used the full potential linear augmented plane wave (FPLAPW) scheme, in the framework of DFT with modified Becke Johnson approximation (mBJ). We present the band structure, density of states (DOS), and electronic charge density. In addition, the band structure calculation suggests that the β-A2 Hg3 Ge2 S8 (A=K and Rb) are semiconductors with indirect band gaps of 2.497 and 2.481 eV for β-K2 Hg3 Ge2 S8 and β-Rb2 Hg3 Ge2 S8 compounds, which is in excellent agreement with the estimated value of 2.7 eV for β-K2 Hg3 Ge2 S8 . An exhaustive study of the electronic density of states and the electronic charge density redistribution reveals the covalent bonding characteristics between Hg, Ge and S atoms. To get the fundamental characteristics of these two compounds, we have probe their linear optical properties such as the dynamic dielectric function, energy loss function, reflectivity, refractive index and absorption coefficients, In the energy range of 0–15 eV. From the dynamic dielectric constant, the structural anisotropy is clearly observed. Optical response study recommends that the imaginary part of dielectric function spectra is appropriated for to be the interband transition.